Asthma costs and social impact - Nunes, C (2017)
In recent decades, both asthma prevalence and incidence have been increasing worldwide, not only due to the genetic background, but mainly because of the effect of a wide number of environmental and lifestyle risk factors. In many countries noncommunicable diseases, like asthma, are not yet considered a healthcare priority. This review will analyze and discuss disparities in asthma management in several countries and regions, such as access to healthcare human resources and medications, due to limited financial capacity to develop strategies to control and prevent this chronic disease. This review tries to explore the social and economic burden of asthma impact on society. Although asthma is generally accepted as a costly illness, the total costs to society (direct, indirect and intangible asthma costs) are difficult to estimate, mainly due to different disease definitions and characterizations but also to the use of different methodologies to assess the asthma socio-economic impact in different societies. The asthma costs are very variables from country to country, however we can estimate that a mean cost per patient per year, including all asthmatics (intermittent, mild, moderate and severe asthma) in Europe is $USD 1,900, which seems lower than USA, estimated mean $USD 3,100.